Ảnh hưởng của chất lượng hoạt động kiểm toán nội bộ đến hành vi điều chỉnh lợi nhuận: Nghiên cứu thực nghiệm tại các công ty niêm yết trên thị trường chứng khoán Việt Nam - Trần Thị Giang , Tân; Tăng Thị Thanh , Thuỷ (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The research aims to examine the impact of internal auditing quality on accruals-based earnings management by manipulating accounting policies in listed companies in Vietnam. The data were collected from 92 listed companies (368 observations) in HOSE and HNX from 2014 to 2017. The research findings show that internal auditing quality is measured by competence, objective and internal auditing size have negative influences on accruals-based earnings management. Based on this result, the authors suggest that the listed companies must have established high-quality internal audit department, especially in internal auditing’s competence, objective and size as an important monitoring component on earnings management of manager. In terms of audit, when using internal auditors, it is necessary to pay attention to the quality of internal audit activities reflecting through competence, objectivity, and size of internal audit in order to determine the scope, content and subsequent audit procedures.